'Revolutions, philosophical as well as civil': French chemistry and American science in Samuel Latham Mitchill's Medical Repository. Issue 2 (2nd April 2020) - Apel, Thomas
ABSTRACT: From 1797 to 1801 a controversy played out on the pages of the Medical Repository, the first scientific journal published in the United States. At its centre was the well-known feud between the followers of Antoine Lavoisier and Joseph Priestley, the lone supporter of the phlogiston model. The American debate, however, had more than two sides. The Americans chemists, Samuel Latham Mitchill and Benjamin Woodhouse, who rushed to support Priestley did not defend his scientific views. Rather, as citizens of a republic, they defended his right to have them. They also castigated the assertions of the "French chemists, " whose claims that the new chemistry obviated debate seemed unsettlingly similar to the dictatorial ambitions of the French state. Using the Medical Repository, Mitchill and Woodhouse sought a compromise that validated the new chemistry, but united it with a more egalitarian form of discourse. The desired balance eluded them. Priestley proved too stubborn, and as the French Revolution descended into dictatorship and war, Mitchill and Woodhouse came more to realize that truly prising French chemistry from the culture of the revolutionary era. The episode left Mitchill and Woodhouse disillusioned with chemistry and hoping to redirect scientific enthusiasm to more pious ends.